Analysis of changes in bacterial diversity in healthy and bacterial wilt mulberry samples using metagenomic sequencing and culture-dependent approaches - Yuan, Ting; Qazi, Izhar Hyder; Li, Jinhao; Yang, Peijia; Yang, Hongyu; Zhang, Xueyin; Liu, Weili; Liu, Jiping (Frontiers in Plant Science, 2023)
Introduction Mulberry bacterial wilt is a serious destructive soil-borne disease caused by a complex and diverse group of pathogenic bacteria. Given that the bacterial wilt has been reported to cause a serious damage to the yield and quality of mulberry, therefore, elucidation of its main pathogenic groups is essential in improving our understanding of this disease and for the development of its potential control measures. Methods In this study, combined metagenomic sequencing and culture-dependent approaches were used to investigate the microbiome of healthy and bacterial wilt mulberry samples. Results The results showed that the healthy samples had higher bacterial diversity compared to the diseased samples. Meanwhile, the proportion of opportunistic pathogenic and drug-resistant bacterial flora represented by Acinetobacter in the diseased samples was increased, while the proportion of beneficial bacterial flora represented by Proteobacteria was decreased. Ralstonia solanacearum species complex (RSSC), Enterobacter cloacae complex (ECC), Klebsiella pneumoniae, K. quasipneumoniae, K. michiganensis, K. oxytoca, and P. ananatis emerged as the main pathogens of the mulberry bacterial wilt. Discussion In conclusion, this study provides a valuable reference for further focused research on the bacterial wilt of mulberry and other plants.